Glamorous Wig Company / Carlneno Jison ... [et al.] - Jison, Carlneno; Asno, Norazian; Rahimuddin, Norul Jannah Masithoh; Abd Gani, Nur Fifi Suryanie; Jaimin, Rannol (2009)
Each business plan has a specific purpose to achieve the target in every decision in business. Glamorous Wig also had prepared with clear and specific purposes in the particular plan. One of it is to fulfil the requirement of the basic ETR (ENT 300) subject and also our course subject. As a DPA student in UiTM, our course requires us to do a complete business plan. It is one of our important assignment and compulsory. Another is as the guidance or direction and ways to manage and arrange the business daily activities. It is important especially in making decision and planning in the future objectives for all departments such as in the administration, marketing, financial, operation and not forgetting the human resources management. Next is to examine and evaluate the ability of the competitors and thus to evaluate whether this planned business is able to compete with other competitors in market. In other words we want to know the risk and chance in running this business. To take challenges made by government to increase the participation of Bumiputra in the ENT field is also one of the purposes. The number of Bumiputra who are involved in entrepreneurship is worrying. So, we want set an example to others that we as a Bumiputra is capable to become an entrepreneur.